Discourse Dynamics in Virtual EFL Classrooms: Examining Teacher-Student Talk and Student-Centeredness - Ode, Muhamad Acep; Setyarini, Sri; Purnawarman, Pupung (Universitas PGRI Semarang, 2025)
This study explores how teacher-student talk influences the development of student-centered learning in virtual English as a Foreign Language (EFL) classroom in Indonesia. Using a qualitative narrative inquiry approach, the research investigates the experiences of two EFL teachers, one from a private school and the other from a public school, each with over two years of online teaching experience. Data were collected through written narratives, guided by open-ended prompts, and analyzed thematically. The findings reveal five interrelated themes: teacher-led dynamics, student contributions, strategies for balanced talk, student engagement, and learning outcomes. Results showed that excessive teacher talk, though often necessary for structure and control, can inhibit student participation and motivation. However, when teachers implemented strategies that encourage student voice, such as contextual topics, digital collaboration tools, and dialogic scaffolding, students became more engaged, accountable, and cognitively invested in the learning process. The study concludes that managing discourse balance is essential for effective virtual classroom management and the realization of student-centered instruction. This research contributes to the understanding of discourse as both a pedagogical and relational tool in online EFL contexts and offers practical strategies for teachers seeking to enhance interaction, agency, and engagement in remote learning environments.